National and supranational mechanisms for the protection of human rights and freedoms in contemporary conditions - L. A. Terekhova (Правоприменение)
Subject of the research. The article considers two levels in the mechanism of protection of human rights and freedoms: national and supranational. National includes both judicial and non-judicial methods of protection. The supranational level is represented by universal (global) and regional ways. The purpose of the research is to identify an effective mechanism for the protection of human rights that can replace the mechanism of protection provided by the European Convention for the Protection of Human Rights and Fundamental Freedoms of 1950, which has ceased to be valid for citizens of the Russian Federation. Research methods are the formal-legal method, analysis, synthesis, formallogical method.The main results. Theoretically, a particular citizen can use any of the national and supranational mechanisms for the protection of human rights. However, the nature of their action and the procedure for gaining access to these mechanisms are different, which affects their effectiveness and the readiness of a person to turn to one or another method of protection. Among supranational mechanisms, the Universal Declaration of Human Rights of 1948 has a unique status: on the one hand, this document is “a symbol of the moral consensus of all states, the starting point for the creation of a modern human rights regime”; on the other hand, it is an act-declaration, the application of which in specific legal relations and the protection of human rights with its help are problematic. The International Covenant on Civil and Political Rights of 12/16/1966 provides for the establishment of a Human Rights Committee that exercises control over the provisions of the Covenant through a system of reports. Reports on measures taken to implement the rights provided for by the Covenant, as well as on non-fulfillment of their obligations under the Covenant by other States Parties, are submitted by States Parties. The mechanism of reports, however, is not reliable enough - there are states that ignore it.Regional Conventions are rightly considered the most effective means of protecting human rights. The implementation of the provisions of the Conventions is ensured by the activities of supranational judicial bodies, to which the applicant can file a complaint. The conditions for applying to such a court, its territorial proximity, the possibility of executing court decisions make this method of protection as accessible as possible. Among the national remedies, first of all, it should be noted the activity of the Constitutional Court of the Russian Federation to protect the constitutional rights of citizens. The provisions of the Convention for the Protection of Human Rights and Fundamental Freedoms and the Constitution of the Russian Federation in the section on human rights are almost identical, often written in the same phrases. But, despite the number of coincidences in the designation of human rights and freedoms, the main thing is not the designation (this is a declaration) of a specific right or freedom, but how they are applied and what is the practice of their protection (interpretation) by the Constitutional Court at the national level and the Convention on the supranational. It is here that the understanding of “identical” formulations can differ, and the question of who is better: a national or supranational body protects a particular human right, becomes debatable. It should also be remembered about the very meaning of supranational protection as an opportunity to receive protection from one's own state, albeit a subsidiary one. Therefore, it would be wrong to assume that in the absence of the possibility of applying to the ECHR, a citizen will be able to receive protection in the Constitutional Court without prejudice to the outcome of such protection.Considering that the protection of human rights is, first of all, the activity of national courts of first instance, consideration by the courts of administrative, civil and criminal cases, in cases where it is carried out in full compliance with the norms of procedural legislation, is able to fully ensure the protection of the rights and human freedoms. To do this, the courts have all the necessary tools, you just need the ability and desire to use them.Among the internal structures for monitoring the observance of human rights, a number of state and public bodies can be distinguished - the Commissioner for Human Rights in the Russian Federation, the Council under the President of the Russian Federation for the Development of Civil Society and Human Rights, the Public Chamber of the Russian Federation, the police, the prosecutor's office and others. However, it is not possible to attribute them to the effective bodies for the protection of human rights.Conclusions. The existing national and supranational mechanisms for the protection of human rights, in their effectiveness, are not able to fully compensate for the loss of the opportunity for citizens of the Russian Federation to file a complaint with the European Court of Human Rights.